2014
DOI: 10.5194/isprsarchives-xl-3-25-2014
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Building Extraction From LIDAR Data Covering Complex Urban Scenes

Abstract: ABSTRACT:This paper presents a new method for segmentation of LIDAR point cloud data for automatic building extraction. Using the ground height from a DEM (Digital Elevation Model), the non-ground points (mainly buildings and trees) are separated from the ground points. Points on walls are removed from the set of non-ground points by applying the following two approaches: If a plane fitted at a point and its neighbourhood is perpendicular to a fictitious horizontal plane, then this point is designated as a wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 14 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…Assuming buildings mainly have two principal directions along its length and width, the lines at least 6 m long are considered as long lines [40]. The long lines from the image are kept fixed.…”
Section: Building Footprint Generationmentioning
confidence: 99%
“…Assuming buildings mainly have two principal directions along its length and width, the lines at least 6 m long are considered as long lines [40]. The long lines from the image are kept fixed.…”
Section: Building Footprint Generationmentioning
confidence: 99%
“…Therefore, wall points still exist in the building point clouds obtained by the RIMM algorithm. In order to retain only the rooftop points, we used Awrangjeb's method to remove wall points [42]. The experimental results demonstrated that the wall points were eliminated by this method effectively.…”
Section: Extraction Of Building Rooftop Pointsmentioning
confidence: 99%
“…A high-performance automatic building detection technique [26] has been implemented for this purpose. The extracted buildings are two-dimensional building footprints, where each footprint is a polygon showing the boundary of each building.…”
Section: Proposed Approachmentioning
confidence: 99%
“…Points on the neighbouring planar segments are accumulated to form individual building regions. An algorithm is employed to regularise the building boundary [26]. Lines along the boundary are first extracted, and then, the short lines are adjusted with respect to the long lines through maintaining the parallel and perpendicular property among the lines.…”
Section: Automatic Building Extractionmentioning
confidence: 99%
See 1 more Smart Citation